2013
DOI: 10.3233/thc-130764
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of upper extremity reachable workspace using Kinect camera

Abstract: BACKGROUND: In clinical evaluation of upper extremity, there is a lack of assessment methods that are quantitative, reliable, and informative of the overall functional capability of an individual. OBJECTIVE: We present new methodology for the assessment of upper extremity impairments based on the concept of 3dimensional reachable workspace using Microsoft Kinect. METHODS: We quantify the reachable workspace by the relative surface area representing the portion of the unit hemisphere that is covered by the hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 32 publications
3
114
0
Order By: Relevance
“…Taking advantage of currently available unobtrusive markerless sensor technology, a novel upper extremity outcome measure based on Kinect sensor-acquired 3-dimensional (3D) reachable workspace was recently developed by the study investigators 13,14 and applied in FSHD. 15 In a previous study, the novel reachable workspace outcome measure demonstrated its validity against the upper extremity-specific components of the FSHD evaluation scale (subscale II: scapular girdle; subscale III: upper limb).…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd)mentioning
confidence: 99%
“…Taking advantage of currently available unobtrusive markerless sensor technology, a novel upper extremity outcome measure based on Kinect sensor-acquired 3-dimensional (3D) reachable workspace was recently developed by the study investigators 13,14 and applied in FSHD. 15 In a previous study, the novel reachable workspace outcome measure demonstrated its validity against the upper extremity-specific components of the FSHD evaluation scale (subscale II: scapular girdle; subscale III: upper limb).…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd)mentioning
confidence: 99%
“…At this point it's unclear if virtual targets are as useful as real-life targets. Recent studies using the Kinect depth sensor for upper extremity function and workspace analysis [13][14][15] are promising and should be carefully designed with the results of this study in mind.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of recent studies, [6][7][8][9][10][11][12] the utility of a novel upper extremity reachable workspace outcome measure, acquired using a 3D vision-based sensor, have demonstrated promising potential in various neuromuscular disorders. Specifically in DMD, the Kinect sensor-based reachable workspace RSA has been demonstrated to be applicable, reliable, and valid in both pediatric and adult populations with DMD, as well as ambulatory and nonambulatory individuals with a wide range of upper limb impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute total and quadrant reachable workspace surface envelope areas (m 2 ) were calculated and normalized by each individual's arm length to obtain the RSA. 6,7 This RSA representing the portion of a frontal unit hemi-sphere, is determined by dividing the absolute reachable workspace area by the factor 4pr 2 3 (1/2), where r represents the arm length. This provides normalization of the data by each individual's arm length to allow comparison between subjects.…”
Section: Reachablementioning
confidence: 99%
See 1 more Smart Citation